Stereoselective Organic Reactions in Heterogeneous Semiconductor Photocatalysis - Kohtani, Shigeru; Kawashima, Akira; Miyabe, Hideto (Frontiers in Chemistry, 2019)
The most significant feature of heterogeneous semiconductor photocatalysis is that both oxidation and reduction occur in a one-pot process. Thus, photocatalysis leads to unique redox organic reactions that cannot be achieved by conventional techniques using oxidants or reductants. Semiconductor photocatalysis is expected to be a new method for fine chemical syntheses of highly valuable molecules such as chiral medicines. However, the use of semiconductor photocatalysts in stereoselective reactions has been limited so far. This mini-review highlights recent progress in stereoselective organic reactions using semiconductor photocatalysts, briefly summarizing the enantio- and diastereoselective reactions based on the currently available literature.